Fairness in Polygamy : An Analysis of Islamic Legal Literature and Social Reality - Ahmad Rofi'i Harahap (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2024)
The fulfilment of fair financial support is a central challenge in the practice of polygamy in Muslim societies. From an Islamic legal perspective, the husband's obligation to provide for his wives fairly and proportionally is a key prerequisite for the validity of polygamy. This study aims to analyse the principle of fairness in maintenance in polygamy by exploring the normative views of Islamic law and comparing them with the social reality. Through library research, this study analyses primary sources of Islamic law (fiqh books and nash) as well as secondary sources such as journals and legislation. The results reveal that although Islamic law stipulates fairness in financial support as an absolute obligation with clear legal consequences, its implementation in practice varies greatly. This variation is influenced by factors such as education, economic conditions, and religious awareness. These findings highlight a significant gap between the ideal norm and its practice, which often leads to injustice and domestic conflict. Therefore, this study emphasises the urgency of pre-marital guidance, strengthening legal literacy, and social supervision to ensure that the principle of alimony justice can be realised in the practice of polygamy.